Modulation in Electronics and Telecommunications - Dekoulis, George (IntechOpen, 2020)
The book presents new results of research advancing the field and applications of modulation. The information contained herein is important for improving the performance of modern and future wireless communication systems (CS) and networks. Chapters cover such topics as amplitude modulation, orthogonal frequency-division multiplexing (OFDM) signals, electro-optic lithium niobate (LiNbO3) modulators for optical communications, radio frequency signals, and more.